Marketing to women using social media - Buchanan, Holly (Henry Stewart Talks, 2012)
Why you need to use social media to market to women, A woman's buying process and how it's different from a man's buying process, What marketing elements are effective with women, Social media strategy, What is your brand's voice, Online video, Blogs, Blogger outreach, Twitter, Facebook